2017
DOI: 10.2147/ppa.s129088
|View full text |Cite
|
Sign up to set email alerts
|

Patient knowledge and pulmonary medication adherence in adult patients with cystic fibrosis

Abstract: Background and objectivesPatient knowledge of lung function (ie, forced expiratory volume in 1 s [FEV1]% predicted) and the intended benefits of their prescribed pulmonary medications might play an important role in medication adherence, but this relationship has not been examined previously in patients with cystic fibrosis (CF).MethodsAll patients diagnosed with CF and without prior lung transplantation were invited to complete knowledge and self-reported medication adherence questionnaires during routine out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
2
9
0
1
Order By: Relevance
“…Knowledge about treatment has regularly been identified as a theme in qualitative studies (Sawicki et al ., ). However, consistent with studies showing no relationship between knowledge and adherence (Lin, Kendrick, Wilcox, & Quon, ; Modi & Quittner, ), this study shows that most participants report that they have good levels of knowledge. This is consistent with a systematic review that showed that knowledge is necessary but not sufficient to promote medication adherence (Kahwati et al ., ).…”
Section: Discussionsupporting
confidence: 90%
“…Knowledge about treatment has regularly been identified as a theme in qualitative studies (Sawicki et al ., ). However, consistent with studies showing no relationship between knowledge and adherence (Lin, Kendrick, Wilcox, & Quon, ; Modi & Quittner, ), this study shows that most participants report that they have good levels of knowledge. This is consistent with a systematic review that showed that knowledge is necessary but not sufficient to promote medication adherence (Kahwati et al ., ).…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that the differences of medication literacy in hypertensive patients with different levels of education were mainly manifested in the two dimensions of knowledge and skill literacy, which was similar to Newman et al [22]. However, Lin et al [23] found that knowledge related to disease was irrelevant to medication adherence. In the study, the knowledge and skill literacy of patients with education of high school or technical secondary school was significantly higher than that of patients with junior middle school or below.…”
Section: Education Level Influencing On Level Of Medication Literacy supporting
confidence: 71%
“…Good tolerability of dornase alfa therapy, minimum treatment burden and time requirement play more important roles in medication adherence 44,45 . TOPIC 6.…”
Section: Statementmentioning
confidence: 99%